Ending Mass Incarceration: Why It Persists and How to Achieve Meaningful Reform - Beckett, Katherine (Studies in Crime and Public Policy Ser., 2022)
Ending Mass Incarceration explores why mass incarceration is a failed public safety strategy and what should be done to bring about truly transformative change. Although policymakers on both the left and right now recognize mass incarceration as a problem rather than a solution, and many states have taken steps to reduce prison populations, the criminal legal response to crime is harsher than ever. This book identifies three key dynamics that are bolstering mass incarceration. It also identifies three broad changes that would limit the power and reach of the criminal legal system while also addressing the social problems to which it is a misguided response.